The Impact of Promotional Strategies of Pharmaceutical Companies on Doctor’s Recommendation of Branded Drugs: An Empirical Study on Pharmaceutical Industry in Sri Lanka. - Punchibandara, M. M. T. (8th International Conference on Business & Information ICBI – 2017, Faculty of Commerce and Management Studies, University of Kelaniya, Sri Lanka., 2017)
The study was focused on selected promotional strategies such as medical detailing, providing scientific materials, Sponsorships, continuous medical education programs (CME), and sponsoring clinical meetings conducted by the pharmaceutical companies in order to get recommendations of their products. As a sample, 150 doctors from Colombo, Kandy and Galle, were interviewed with a structured questionnaire. Both descriptive and inferential statistics methods were used to analyze the data. Correlation analysis and multiple regressions were used to test the relationship among the independent and dependent variables. The statistical analysis revealed that there is a significant influence of promotional strategies used by pharmaceutical companies on the recommendation of branded drugs by doctors. Further, it was found that each promotional strategy has different degree of impact on recommendation of branded drugs. Detailing and sampling have significant impact but it is relatively low compared to other factors like continuous meetings, scientific materials and CME.
Keywords: Pharmaceutical Industry; Branded Drugs; Promotional Strategies